Predictors of multidrug- and extensively drug-resistant tuberculosis in a high HIV prevalence community. - Andrews, Jason R; Shah, N Sarita; Weissman, Darren; Moll, Anthony P; Friedland, Gerald; Gandhi, Neel R (PloS one, 2010)
Multidrug-resistant (MDR) and extensively drug-resistant (XDR) tuberculosis (TB) have emerged in high-HIV-prevalence settings, which generally lack laboratory infrastructure for diagnosing TB drug resistance. Even where available, inherent delays with current drug-susceptibility testing (DST) methods result in clinical deterioration and ongoing transmission of MDR and XDR-TB. Identifying clinical predictors of drug resistance may aid in risk stratification for earlier treatment and infection control.
Keywords: Adult; Case-Control Studies; Communicable Disease Control; Extensively Drug-Resistant Tuberculosis; Female; HIV Infections; Humans; Male; Odds Ratio; Prevalence; Retrospective Studies; Risk; Risk Factors; South Africa; Tuberculosis, Multidrug-Resistant